It happened in the Cimarron country - Zimmer, Stephen; Lewis, Steve (Parker, Colo. : Eagle Trail Press, 2013)
This book focuses on the people of the cimarron Country, telling the stories of more than two dozen hardy residents who made homes for themselves and others in this rugged land.
A Double Z Bar Ranch book.
100944
Keywords: New Mexico -- Colfax County; New Mexico -- Cimarron Canyon; Cimarron (N.M.) -- History